THE USE OF IRONY AND SATIRE IN THE CANTERBURY TALES - Eldorbek Erkin og’li Khamitov; Turabayeva Ruhshona O’ktambekovna (TADQIQOTLAR, 2026)
Abstract This study investigates Geoffrey Chaucer’s use of irony and satire in The Canterbury Tales, focusing on how these literary tools critique the social, religious, and moral norms of 14th-century England. Chaucer’s irony frequently highlights the gap between appearance and reality, revealing hypocrisy, human weaknesses, and pretentious behavior. Through satire, he examines the conduct of different social groups—including the clergy, nobility, and peasants—showing the contrast between idealized values and actual practices. The paper analyzes key tales such as the Miller’s Tale, the Wife of Bath’s Tale, and the Summoner’s Tale, illustrating how humor, exaggeration, and irony are combined to expose vices like greed, lust, pride, and corruption. Chaucer’s use of multiple narrative voices allows readers to experience a layered social commentary, making the work both entertaining and thought-provoking. Moreover, this research emphasizes the lasting impact of Chaucer’s techniques. His skillful blending of irony and satire not only portrays the complexities of medieval society but also offers a framework for understanding human behavior and societal critique in literature. Chaucer’s narrative strategies have influenced subsequent literary traditions, particularly in the use of humor as a method to reflect on social and moral issues.